2008
DOI: 10.1186/1471-2458-8-191
|View full text |Cite
|
Sign up to set email alerts
|

Post-graduation migration intentions of students of Lebanese medical schools: a survey study

Abstract: Background: The international migration of physicians is a global public health problem. Lebanon is a source country with the highest emigration factor in the Middle East and North Africa and the 7th highest in the World. Given that residency training abroad is a critical step in the migration of physicians, the objective of this study was to survey students of Lebanese medical schools about their intentions to train abroad and their post training plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 17 publications
2
55
3
1
Order By: Relevance
“…10,[14][15][16][17][18] As for this study, other studies [7][8][9]28 reported that many students were not sure of their future area of specialization. In many other developing countries, the critical step in the migration of medical graduates is the moment when they decide to obtain specialized training: a frequent individual decision is to look for it abroad, 7,[28][29][30] leading to a subsequent decision to stay in the host country. 28 Reflecting the lack of specialist training in the country, students in Cape Verde would like to obtain specialized training abroad.…”
Section: Discussionmentioning
confidence: 99%
“…10,[14][15][16][17][18] As for this study, other studies [7][8][9]28 reported that many students were not sure of their future area of specialization. In many other developing countries, the critical step in the migration of medical graduates is the moment when they decide to obtain specialized training: a frequent individual decision is to look for it abroad, 7,[28][29][30] leading to a subsequent decision to stay in the host country. 28 Reflecting the lack of specialist training in the country, students in Cape Verde would like to obtain specialized training abroad.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done in Lahore (60.4%) of the students intended to train abroad either for a specialty (54.9%) or a subspecialty (5.5%) while 10% were not clear about their future intentions (Imran et al 2011). Lastly, it is far less than the result of a study done in Lebanon, which showed 96% of students prefer to study abroad (Akl et al 2008). Medicine was the most selected specialty among whole group and each subgroup abroad or local training preference; the same preference was documented in other studies conducted in Iraq and Germany (Yang 2007) (Mpinganjira 2009) (McCarthy et al 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Indian-Americans from many sectors are moving back to India, where economic opportunities for returnees are on the rise, and quality of life is, in many respects, superior to the U.S. (Roy, 2009). Similarly, nearly a quarter of Lebanese medical students who intended to train abroad wished to return to their native country immediately after completing their training-perhaps more relevant to my mother's point, as Lebanon is considered a middle-tohigh-income country with adequate infrastructure, existing health systems and economic stability to offer its healthcare work force (Akl et al, 2008). Though brain circulation is a component in addressing brain drain, it is improbable that it will be a stand-alone solution.…”
Section: Stemming the Medical Brain Drain: A Personal Perspective On mentioning
confidence: 99%